Celebrating Birthdays for Harry Dalva, Peggy Wilson, and Maril Turpin at home of Shirley Griffenhagen and Maril Turpin - Watkins, Howard::::::::: (1978)
Jeanie Olgesby, Frances Kamp, Christine Watkins, Peggy Wilson, John Olgesby standing in pool; lounge chairs